Exploration of Teachers' Creative Thinking Ability Profile in Implementing Chemistry Learning in Senior High Schools - Jesi J. Pongkendek; Diana Rochintaniawati (Universitas Tadulako, 2025)
This study addresses the limited empirical evidence regarding chemistry teachers’ creative thinking performance in Indonesia. To fill this gap, the present research aims to explore the creative thinking ability profile of senior high school chemistry teachers. This quantitative descriptive study employed an exploratory design and included 21 chemistry teachers from various provinces in Indonesia. Data were collected using a validated creative thinking questionnaire consisting of four indicators: fluency, flexibility, originality, and elaboration. The results indicated that 66.67% of teachers were in the “Very Good” category, 28.57% in the “Good” category, and only 4.76% in the “Fair” category. Among the indicators, fluency showed the highest average score (91.23%), followed by elaboration (86.67%), flexibility (84.95%), and originality (80.38%). These findings indicate that chemistry teachers demonstrate strong abilities in generating and elaborating ideas. At the same time, originality remains comparatively lower due to systemic constraints such as inflexible education policies and limited pedagogical autonomy. The study also highlights the importance of institutional support, training programs, and collaborative learning environments that promote pedagogical creativity among teachers. Enhancing originality, in particular, requires schools to provide more autonomy and flexibility in instructional planning. Ultimately, the results of this study can serve as a reference for educational policymakers and curriculum developers in designing teacher development programs that not only improve content delivery but also cultivate innovative teaching mindsets, essential for meeting the demands of 21st-century learning.